Annoyance of low-level tonal sounds – Factors affecting the penalty. (October 2017) - Oliva, David; Hongisto, Valtteri; Haapakangas, Annu
Abstract: Purpose: Environmental and appliance sounds involving tonal components can be more annoying than broad-band noise. Mandatory penalty values exist in many countries for tonal sound. The purpose of our study was to determine how tonal sounds are perceived compared to non-tonal sounds at overall levels close to typical regulated levels inside residential dwellings. Methods: Forty participants rated the loudness and annoyance of tonal sounds and non-tonal reference sounds in laboratory conditions. The tonal frequencies were 50, 110, 290, 850 and 2100 Hz. Four levels of tonal audibility were used: 5, 10, 17 and 25 dB. The experiment was repeated using two overall levels of tonal sounds: 25 and 35 dB L Aeq . Penalty was determined by finding an equally annoying reference sound. Results: The penalty depended on the tonal frequency and the tonal audibility. Penalty values were also different with different overall levels especially at high tonal frequencies. Annoyance penalty was zero at two lowest tonal frequencies 50 and 110 Hz. At other tonal frequencies, the penalty increased with increasing tonal audibility and tonal frequency. The largest value of penalty was 12 dB. It was obtained at tonal frequency 2100 Hz and with the largest level of tonal audibility. Conclusions: Our results are against the use of fixed penalty values, which are usual in many national regulations, when the overall level is low, within 25 and 35 dB L Aeq . The results support the application of a step-wise penalty where the penalty depends on tonal frequency, tonal audibility and overall level. Graphical abstract: Highlights: Penalty is usually applied for tonal sounds because it can be annoying. This is the first study exploring the penalty of tonal sounds below 35 dB LAeq. Penalty was found to depend on tonal frequency and tonal audibility. The penalty was 0 dB below 200 Hz and up to 12 dB above 2000 Hz. Findings are against constant penalty and for step-wise penalty systems.